Upaya Hukum Masyarakat Kelurahan Sri Meranti Kota Pekanbaru terhadap Pemenuhan Hak Masyarakat dalam Peraturan Daerah Provinsi Riau Nomor 6 Tahun 2012 - Shandy Utama, Andrew (Melayunesia Law, 2018)
Corporate Social Responsibility/CSR is the responsibility inherent in every company to keep creating a harmonious, balanced, and appropriate relationship with the local communitys environment, values, norms and culture. However, CSR implemented by PT Riau Crumb Rubber Factory is very minimal perceived by the community of Sri Meranti Village. The problem is how is the legal effort of the community of Sri Meranti to the fulfillment of community rights in Riau Provincial Regulation Number 6 of 2012? This research is a sociological law research. The result of this research is if there are companies in Riau Province that donât implement CSR to society residing in company location, hence pursuant to Article 32 Riau Provincial Regulation Number 6 of 2012, the company may be subject to administrative sanction by Government of Riau Province in the form of reprimand written and other forms of sanction in accordance with the laws and regulations. Therefore, the legal effort that can be done by the community of Sri Meranti Village if PT Riau Crumb Rubber Factory doesnât implement CSR, the community of Sri Meranti Village can convey their aspiration to the Regional House of Representatives of Riau Province so that the company is recommended to receive administrative sanction from the government.